- Perlindungan Konsumen atas Pemberlakuan Penggunaan Ulang Nomor Pelanggan menurut Undang-Undang Perlindungan Konsumen: - - Helmy Rajendra Inzaghi; Pringgodani Sanusi, Heru (Faculty of Law, Universitas Trisakti, 2023)
Reusing Customer Numbers is a topic that is quite hotly discussed by the public. The public considers that reusing customer numbers is detrimental to consumers, especially if the old cell phone number user has a track record that is not good in using the number. The formulation of the problem is how is the government's policy in enforcing the reuse of customer numbers and how do consumers get their rights restored for losses suffered as a result of reusing customer numbers according to UUPK. This article is a normative research, descriptive in nature, and uses secondary and primary data as research supporting data, using qualitative analysis which also draws deductive conclusions. The results: the government in its policy and authority as a regulator issued the Minister of Communication and Informatics Regulation Number 14 of 2018 concerning the Basic National Telecommunications Technical Plan. Based on the discussion, this regulation has binding legal force because it is in accordance with the statutory hierarchy, the author also finds that in enforcing the re-use of customer's own numbers, there is no resolution of complaints related to the use of own cellular numbers. Conclusion: consumers' rights to comfort and safety have not been fulfilled.